2020
DOI: 10.1016/j.cub.2019.11.086
|View full text |Cite
|
Sign up to set email alerts
|

A Cycle of Ubiquitination Regulates Adaptor Function of the Nedd4-Family Ubiquitin Ligase Rsp5

Abstract: In yeast, the main ubiquitin ligase responsible for the sorting of proteins to the lysosomal vacuole is Rsp5, a member of the Nedd4 family of ligases whose distinguishing features are a catalytic HECT domain and 3 central WW domains that bind PY motifs in target proteins. Many substrates do not bind Rsp5 directly, and instead rely on PY-containing adaptor proteins that interact with Rsp5. Recent studies indicate that the activities of these adaptors are elevated when they undergo ubiquitination, yet the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 70 publications
(115 reference statements)
1
43
0
Order By: Relevance
“…Interestingly, we found that Pil1 was rapidly dephosphorylated upon raffinose treatment ( Fig. 5 C); our optimised SDS-PAGE ( MacDonald et al, 2020 ) revealed a marked shift from slower to faster migrating dephosphorylated bands that have been previously correlated with increased Pil1 assembly at eisosomes ( Walther et al, 2007 ). Mup1–GFP- and Pil1–mCherry-expressing cells, in both glucose and raffinose media, were used for Slimfield imaging ( Fig.…”
Section: Resultssupporting
confidence: 54%
“…Interestingly, we found that Pil1 was rapidly dephosphorylated upon raffinose treatment ( Fig. 5 C); our optimised SDS-PAGE ( MacDonald et al, 2020 ) revealed a marked shift from slower to faster migrating dephosphorylated bands that have been previously correlated with increased Pil1 assembly at eisosomes ( Walther et al, 2007 ). Mup1–GFP- and Pil1–mCherry-expressing cells, in both glucose and raffinose media, were used for Slimfield imaging ( Fig.…”
Section: Resultssupporting
confidence: 54%
“…However, the detailed underlying mechanisms are still unclear. Rsp5 can interact with substrates via the PY motif (Pro‐Pro‐X‐Tyr) (Baile et al, 2019; MacDonald, Shields, Williams, Winistorfer, & Piper, 2020). Some substrates contain the PY motifs, whereas others lacking the PY motifs are dependent on adaptor proteins (Art1‐10, Bul1/2) that recruit Rsp5 to substrates (Ghaddar et al, 2014; Lin, MacGurn, Chu, Stefan, & Emr, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…3 J ). It was reported that adaptor protein overexpression interferes with other noncognate Rsp5-dependent processes ( MacDonald et al, 2020 ). We therefore asked if the Rsp5 pool is depleted due to enhanced Rsp5 recruitment to Rcr1.…”
Section: Resultsmentioning
confidence: 99%